Economic Inequality Is Linked to Biased Self-Perception - Loughnan, Steve (2011)
People’s self-perception biases often lead them to see themselves as better than the average person (a phenomenon known as self-enhancement). This bias varies across cultures, and variations are typically explained using cultural variables, such as individualism versus collectivism. We propose that socioeconomic differences among societies—specifically, relative levels of economic inequality—play an important but unrecognized role in how people evaluate themselves. Evidence for selfenhancement was found in 15 diverse nations, but the magnitude of the bias varied. Greater self-enhancement was found in societies with more income inequality, and income inequality predicted cross-cultural differences in self-enhancement better than did individualism/collectivism. These results indicate that macrosocial differences in the distribution of economic goods are linked to microsocial processes of perceiving the self.